Analysis of risk factors and comorbidities associated with mortality of hospitalized patients with Covid-19 in the high sertão of Paraiba (Research, Society and Development, 2022)
The current Covid-19 pandemic is an international public health problem, given the consequences generated by its existence. In view of this scenario, the study aimed to identify and evaluate the impact of risk factors and comorbidities associated with the mortality of patients hospitalized with Covid-19 in Alto Sertão Paraibano. It is an exploratory, descriptive and analytical study. The research used data extracted from the SIVEP database through OpenDataSUS, from March 2020 to August 2021. In the data analysis, descriptive statistical techniques were used. Regarding the results in the years 2020 and 2021, respectively, we had the variables female (52.9%) and (42.8%), male (47.1%) and (57.2%), place of residence Urban Zone (78.4%) and (77.1%), Rural Zone (21.6%), and 22.9%) and as for symptoms, cough, dyspnea, hyposaturation and respiratory distress had the highest percentages in both the years under study and regarding the presence or absence of risk factors, it was found that most of them had some risk factor or comorbidities. Therefore, the analysis provides an overview of the Pandemic and the determining factors in this process in the municipalities of Alto Sertão Paraibano and the eligible variables showed that symptoms and comorbidities were significant predictors for hospitalization and disease evolution, and the outcome for death and/or cure.